The Drosophila DEG/ENaC PPK12 is a Na+ leak channel with a low Na+ affinity - Lu Qin; Nikita Komarov; Cornelia Fritsch; Simon G. Sprecher; Stefan Gründer; Dominik Wiemuth (Scientific Reports)
Abstract DEG/ENaC ion channels have various functions in different organisms. In Drosophila, DEG/ENaCs are named Pickpockets (PPKs) and form a large insect-specific radiation with seven subfamilies containing 31 members. Several different functions have been proposed for PPKs, including salt and water taste. However, despite their many functions, most PPKs have not been functionally characterized in heterologous expression systems, leaving their functional properties unknown. Here, we expressed six PPKs in Xenopus oocytes, which are expressed in the chemosensory system of Drosophila larvae. We found that PPK12 forms a constitutively open ion channel that is permeable to Na+ ions. PPK12 currents do not saturate even at high Na+ concentrations, suggesting that PPK12 may be involved in sensing high salt concentrations. Our study shows that at least some PPKs are amenable to functional characterization in Xenopus oocytes, allowing to elucidate the relation of their functional properties with their proposed functions in the organism.